The Role of Honey in Reproductive Age Gynecological Diseases: An Overview of Clinical Trials - Masoumeh Norouzi Allahleh Korabi; Maedeh Rezghi (Tehran University of Medical Sciences, 2024)
Honey has been used since ancient times to treat various diseases such as gynecological diseases. The current study aims to investigate clinical trials related to the therapeutic effects of honey on women's diseases. Databases including Web of Science, Scopus, PubMed, Google scholar, and SID were investigated for clinical studies focusing on honey in gynecological diseases up to 31 June 2022. Eligibility was checked based on selection criteria. Twenty-five clinical trials met the inclusion criteria. Therapeutic properties of honey and its compounds as a systemic and/or local treatment on vulvovaginal candidiasis, cervicitis, dysmenorrhea, premenstrual syndrome, labor pain, episiotomy and cesarean wounds, nipple fissure, breast cancer and intrauterine insemination (IUI), with the mechanisms of action of antibacterial, antifungal, anti-inflammatory, wound healing, analgesic, antioxidant and anticancer activities have been proven. It was also found that phenolic compounds including flavonoids and phenolic acids are the main ones responsible for most of these therapeutic effects of honey. This study supports the healing properties of honey in gynecological diseases at reproductive age. Also, in the current studies, honey proved safe with minor adverse effects. Of course, to achieve definitive conclusions about the effectiveness and safety of honey, it is necessary to conduct more clinical trials with a larger sample size, appropriate intervention duration, and optimal doses in future studies.